2007
DOI: 10.1016/j.bbamcr.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin dynamics during DSB repair

Abstract: We show that double strand breaks (DSBs) induced in chromatin of low as well as high density by exposure of human cells to gamma-rays are repaired in low-density chromatin. Extensive chromatin decondensation manifested in the vicinity of DSBs by decreased intensity of chromatin labelling, increased H4K5 acetylation, and decreased H3K9 dimethylation was observed already 15 min after irradiation. Only slight movement of sporadic DSB loci for short distances was noticed in living cells associated with chromatin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 40 publications
9
102
1
Order By: Relevance
“…Considering that the volume of a typical mammalian cell nucleus is about 250 mm 3 , a single treatment can, thus, result in multiple accidental DSB interactions leading to chromosome rearrangements. Fusions between IRIF have been reported in cells exposed to alpha particles (Aten et al, 2004) and X-rays (Falk et al, 2007). Thus, the 2.2-and 3.2-fold increases in nuclear area roamed by DSBs induced by ionizing radiation and etoposide, when compared with that of undamaged chromatin, would be expected to increase the probability of DSB interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the volume of a typical mammalian cell nucleus is about 250 mm 3 , a single treatment can, thus, result in multiple accidental DSB interactions leading to chromosome rearrangements. Fusions between IRIF have been reported in cells exposed to alpha particles (Aten et al, 2004) and X-rays (Falk et al, 2007). Thus, the 2.2-and 3.2-fold increases in nuclear area roamed by DSBs induced by ionizing radiation and etoposide, when compared with that of undamaged chromatin, would be expected to increase the probability of DSB interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Falk et al, 2007;Ziv et al, 2006). It is tempting to speculate that low-density chromatin would be more mobile than condensed chromatin.…”
Section: Irif Mobility Depends On Chromatin Organization and Varies Wmentioning
confidence: 99%
“…Third is that the demethylase activity of KDM4D facilitates the accessibility of ATM kinase to its substrates, which can be achieved by relaxing the chromatin structure through local demethylation of H3K9me2/me3 surrounding the DNA damage sites. Indeed, it was shown that the levels of H3K9me2/3 in γH2AX-positive regions decrease after damage (29,45).…”
Section: Kdm4d Affects the Ir-induced Foci Formation Of Rad51 And 53bp1mentioning
confidence: 99%
“…56 Moreover, decrease in the levels of H3K9me2/3 at gH2AX-positive regions was reported at 20 minutes after IR in mammalian cells. 87 Similarly, Young and colleagues observed local reduction in H3K9me3 levels at sites of damage in cells expressing low to moderate levels of EGFP-KDM4B fusion. 57 In contrast, a recent study reported local increase in H3K9me2/3 at DSB sites, 88 suggesting that H3K9 methylation levels at DNA damage sites are highly dynamics and might be also influenced by the chromatin context at the DNA breakage sites.…”
Section: Dna Damage-induced Substrates Of Kdmsmentioning
confidence: 99%